SYNTHESIS AND CHARACTERIZATION OF BARIUM HEXAFERRITE (BHF) COMPOSITE MATERIALS DOPING FLY ASHES, PORLAND CEMENT, VERMICULITE, CRISTALLINE SILICA AS FIRE PROOFING PROTECTION ON STEEL BEAM IN THE OIL REFINERY INDUSTRY - Harahap, Veryyon; Kartika, Siska Ayu (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
In the modern era, the use of technology and fire protection equipment has become part of the needs of the oil refinery industry. This material functions to retain heat from fire with a temperature of 1000 oC. But apart from the convenience provided, it turns out that this material also has negative effects on the body that is exposed to dust. In this research, a composite-based heat-resistant material will be made from natural red sand with a ratio of 50:50 (wt%) between matrix and filler. Composite preparation has been carried out using the wet milling method with toluene media. Barium M-Ferrite as matrix and Fly Ashes, Porland Cement, Vermiculite, Cristalline as fillers which are used as the main raw materials for making composites. From the results of the X-Ray Diffraction (XRD) test on BaFe12O19 powder as a matrix, it shows that the phase formed by a single face and hexagonal crystal structure has lattice parameters a=5.929 Ǻ and c= 23.41 Ǻ space group (P 63/mmc); hexagonal structured composite samples (JCPDS file No. 39-1433). The results of surface analysis using Scanning Electron Magnetic (SEM) show that the composite has the finest and smallest particle sizes. The true density result of the composite is 5.386364 g/cm3.